Protocol for a biomarker discovery study to identify correlates of risk for future tuberculosis disease progression in South African children (INTREPID) - Hamilton,MS; Derks,I; Kaforou,M; Dunbar,R; McNamara,R; Fortune,S; Roy,RB; van,Deventer A; Bosch,C; Dunican,C; van,der Zalm MM; Levin,M; et al. (BMJ Open, 2026)
IntroductionYoung children and children living with HIV are at high risk of progressing to tuberculosis (TB) disease following Mycobacterium tuberculosis (Mtb) exposure and infection, and also of developing severe forms of disease and TB-related mortality. Identifying children who have very early (sub-clinical) TB disease, prior to progression to clinically apparent TB, would mean that TB preventive treatment (TPT) could be more efficiently targeted to this group. Identifying biomarker changes on drug therapy in children with Mtb infection or very early disease could pave the way for the development of tests that can identify which children have viable bacilli and are therefore at increased risk of disease progression. Methods and analysisThe INTREPID study will utilize already collected samples taken from well-phenotyped paediatric cohorts in three clinical studies conducted in South Africa in children <5 years, including a drug-resistant TPT trial (TB-CHAMP), an observational household contact study (IGRA studies), and a prospective diagnostic study (Umoya), all conducted in a setting with a high burden of TB and HIV. We will employ transcriptomic, proteomic, metabolomic, and serology approaches to analyse changes in host blood profiles at every stage along the TB continuum, from Mtb exposure to disease and from children treated for Mtb infection and early TB disease, as well as targeted Mtb antibody analysis. Data on viral co-infections and relevant clinical and epidemiological parameters will be integrated and evaluated to identify the optimal biosignatures that can predict future progression to clinically overt disease in children below 5 years of age, including those living with HIV. Ethics and disseminationThe study protocol received ethical approval from the Stellenbosch University Health Research Ethics Committee (N23/03/025). The study findings will be disseminated through peer-reviewed publications, scientific conferences, and formal presentations to